Clinical and demographic profile of patients with thyroid eye disease in a tertiary eye care centre - Shrestha, Tina; KC, Rajendra; Jha, Prophulla; Shrestha, Noor; Tamang, Ashish (Journal of Chitwan Medical College, 2026)
Introduction: Thyroid eye disease (TED) is an autoimmune inflammatory disorder of the orbit commonly associated with thyroid dysfunction. Understanding its clinical spectrum, thyroid status, and disease activity is crucial for appropriate management.Method: A cross-sectional study was conducted among adults diagnosed with TED at the Department of Ophthalmology, Dhulikhel Hospital, Nepal, from 7 Apr 2024 to 10 Sep 2024 after ethical approval. Patients with unrelated orbital diseases, trauma, or incomplete records were excluded. Demographics, clinical features, thyroid function, ocular findings, disease activity (Clinical Activity Score, CAS), disease severity (EUGOGO classification), and management were recorded. Data were analysed descriptively with mean±SD or median (IQR) for continuous variables, and n(%) for categorical variables using STATA version 14.0.Result: Among 73 TED patients, the mean age was 42.5±13.2 years; 46(63.0%) were female. Most were from Province 3, 55(75.3%). Thyroid function status was hyperthyroidism in 28(38.4%), hypothyroidism in 27(37.0%), and euthyroidism in 18(24.7%). Ocular findings included lid retraction in 29(39.7%), proptosis in 26(35.6%), and diplopia in 9(12.3%). Active disease (CAS≥3) was present in 23(31.5%). Most had mild disease (68.5%). All cases were managed conservatively with lubricants 73(100%).